STUDENT PERFORMANCE IN BASIC STRUCTURAL ANALYSIS: OUTPUT FROM COURSE AND PROGRAM OUTCOMES - Nik Farhanim Imran; Nor Hafida Hashim; Daliah Hasan (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
In the ever-changing field of engineering education, the success of students relies heavily on the effectiveness of teaching methods and assessment strategies in fundamental courses like Basic Structural Analysis. This study analyses student performance over three semesters (20212, 20222, 20224) in the Basic Structural Analysis course, a fundamental part of the Diploma in Civil Engineering curriculum. By examining student results, it can seek to identify performance trends, assess the impact of teaching methods, and evaluate the correlation between student feedback and learning outcomes. The results show a notable decrease in test scores and the achievement of both Program Outcomes (PO) and Course Outcomes (CO), especially during semester 20224. The analysis identifies common issues like cognitive overload from excessive testing and insufficient student engagement in online classes. Based on these findings, the study recommends targeted interventions, including modifying assessment strategies and improving interactive teaching methods, to address the identified challenges and enhance overall student performance. This research highlights the importance of continuous feedback and adaptive teaching strategies in ensuring the effectiveness of foundational courses in civil engineering education, ultimately contributing to the development of skilled engineering professionals.